2014
DOI: 10.1186/1472-6831-14-47
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood caries and its relationship with perinatal, socioeconomic and nutritional risks: a cross-sectional study

Abstract: BackgroundSocioeconomic, perinatal and other life cycle events can be important determinants of the health status of the individual and populations. This study aimed to assess the prevalence of early childhood caries (ECC), perinatal factors (gestational age, teenage pregnancy and birth weight), family income and nutritional risk in children.MethodsA cross-sectional study in which 320 children were examined according to the criteria established by the World Health Organization. A previously validated questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
1
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 18 publications
0
73
1
12
Order By: Relevance
“…It was reported that low socio-economic status was associated with an increased prevalence of ECC. [45][46][47] However, this study failed to show the association between low socio-economic status and increased risk of ECC. This can be explained with two grounds.…”
Section: Discussionmentioning
confidence: 94%
“…It was reported that low socio-economic status was associated with an increased prevalence of ECC. [45][46][47] However, this study failed to show the association between low socio-economic status and increased risk of ECC. This can be explained with two grounds.…”
Section: Discussionmentioning
confidence: 94%
“…The ECC primary etiologic factors are fermentable carbohydrates, oral bacteria with cariogenic potential, and host susceptibility. Currently, social factors as family's low socioeconomic level and cultural factors and the lack of knowledge of the parents on oral health have also been related to ECC etiology [2][3][4][5]. Although the disease can be prevented and caries lesions are potentially reverted at initial stages, frequently the adequate treatment is not provided and the disease develops with the consequent progression of the lesions up to total destruction of the teeth [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was demonstrated in a study in Brazil that used low birth weight as an indicator of mothers' health during pregnancy. The study proved that children with a low birth weight tend to have dental caries (80.4%) due to the abnormal growth of teeth calcification compared to children with a normal birth weight (9.9%) [9].…”
Section: Discussionmentioning
confidence: 85%